Knowledge, attitude and practice regarding tuberculosis among the patients attending a tertiary care hospital in Maharashtra, India: a cross sectional study - Sonawane, Nilesh S.; Patil, Chaitanya R. (International Journal of Advances in Medicine, 2019)
Background: Tuberculosis is major public health problem especially in the low and middle income countries like India. We conducted a study to assess the knowledge, attitude and practice related to tuberculosis among the patients attending our tertiary care institute. Methods: A cross sectional study was conducted in a tertiary care hospital on the patients attending OPD of tertiary care hospital in Maharashtra. The patients with debilitating illness or bed bound patients and those diagnosed and cured of tuberculosis or were on treatment of tuberculosis were excluded from the study. A pretested and designed questionnaire was used to assess the knowledge, attitude and practice about the cause, clinical features and treatment of tuberculosis. Results: The mean age of the study subjects was 43.34±11.23 years with male: female ratio of 1.45. About 16.67% of the subjects stated that cause of TB is bacteria, 51.33% reported that cough was the most common symptom, 58.67% believed that it spreads from person to person and among the people who said it spreads 58.67% said that it can be preventable. Conclusions: About 1/5th of the study subjects expressed the cause of TB is bacteria or germs, and more than ½ believed that TB spreads from person to person. About 2/3rd of the patients felt that TB was a very serious disease; more than ½ of them expressed fear if they were diagnosed with TB but more than ½ of them also expressed rejection if they have a TB patient as a closed one.